1890 Mich. Gen. Stat. 3800 - (:unkn) unknown (My University, 1890)
Tit. 39, § 9113a: Prohibited going armed with a concealed dirk, dagger, sword, pistol, air-gun, stiletto, metallic knuckles, pocket-billie, sand-bag, skull-cracker, slung-shot, razor, or other offensive and dangerous weapon. Violators guilty of a misdemeanor, punished by fine not more than one hundred dollars, or imprisonment not exceeding three months.
Keywords: CARRY - CONCEALED